Association of Sleep Patterns and Lifestyles With Incident Hypertension: Evidence From a Large Population-Based Cohort Study - Lv, Yanling; Jiang, Guanhua; Tan, Xiao; Bao, Wei; Chen, Liangkai; Liu, Liegang (Frontiers in Cardiovascular Medicine, 2022)
Background Adherence to a healthy lifestyle (no smoking, consuming a healthy diet, engaging in physical activity, and maintaining a healthy weight) is recommended in current guidelines for hypertension prevention. However, evidence regarding the association between sleep behaviors, independently and jointly with traditional lifestyle factors, and the risk of hypertension is limited. Methods This prospective study included 165,493 participants who are free of hypertension at baseline from the UK Biobank. Sleep behaviors, including chronotype, sleep duration, insomnia, snoring, and daytime sleepiness were used to construct a healthy sleep score. We also derived a healthy lifestyle score based on smoking status, diet quality, physical activity, and body mass index (BMI). Cox proportional hazards regression models and competing risk analyses were used to estimate the associations of healthy sleep and lifestyle with the risk of hypertension. The population attributable risk percent (PAR%) was estimated for increased cases of hypertension due to poor adherence to a healthy sleep pattern or a healthy lifestyle. Results A total of 10941 incident hypertension cases were documented during a median of 11.8 years of follow-up. The multivariable-adjusted hazard ratio (HR) for hypertension was 0.58 (95% confidence interval [CI]: 0.52, 0.65) for participants with a sleep score of 5 compared with 0–1, and 0.48 (95% CI: 0.43, 0.54) for participants with a lifestyle score of 4 compared with those who scored 0. For joint association, those with a poor sleep pattern and a poor lifestyle had the highest risk of hypertension (HR: 2.41 [95% CI: 2.12, 2.74]). PAR% was 14.7% (95% CI: 12.3%, 17.1%), 20.1% (95% CI: 17.6%, 22.6%), and 31.7% (95% CI: 27.6%, 35.6%) for poor adherence to a healthy sleep pattern, a healthy lifestyle, and the combination of both, respectively. Conclusions Both a healthy sleep pattern and a healthy lifestyle were associated with a lower risk of hypertension, and the benefits of adhering to a healthy sleep pattern complement the well-established lifestyle for the optimal primary prevention of hypertension. These findings support the current perspective that a healthy sleep pattern is an important part of a healthful and productive lifestyle for hypertension prevention.